Spatial gene expression analysis reveals pathological niches in Japanese encephalitis virus neuroinvasion - Yasuko Orba; Yukie Kashima; Koshiro Tabata; Yukari Itakura; Takuma Ariizumi; William W. Hall; Hirofumi Sawa; Yutaka Suzuki; Michihito Sasaki (Proceedings of the National Academy of Sciences, 2025)
Japanese encephalitis virus (JEV) infection causes encephalitis in humans and animals. Following intradermal infection, JEV crosses the blood–brain barrier (BBB) and reaches target cells in the brain parenchyma. However, the cellular dynamics and pathological niches involved in JEV neuroinvasion remain poorly understood. In this study, we investigated the early stages of JEV infection in the mouse brain employing a highly multiplexed spatial transcriptomics platform to map viral RNA and host gene expressions in intact brain sections at a single-cell resolution. Although JEV RNA was undetectable in brain sections at 1-day postinfection (dpi), innate immune responses were transiently activated across the brain. At 4 dpi, we detected limited viral RNA and mapped its spatial distribution, identifying glial cells surrounding microvessels as early targets of brain infection. We further characterized transcriptional changes in infected and surrounding bystander cells, revealing cell-type–specific antiviral responses. Notably, JEV neuroinvasion led to the downregulation of endothelial tight junction genes, indicative of an early event that precedes BBB impairment during subsequent disease progression. Our spatial transcriptomic analysis provides insights into cell-type– and region-specific responses to JEV infection, and highlights the early role of glial cells in shaping the immune response landscape of the brain. These findings greatly improve our understanding of JEV pathogenesis before the onset of clinical encephalitis.